Body-mass index, nutrition and physical activity in children and adolescents with Down syndrome - Ramos, João Victor Brincas; Nascimento, Isabela do Prado; Gomes, Charles da Silva; Kalkmann, Gabriela Ferreira; Santo, Jéssica Aline do Espírito; Novadzki, Iolanda Maria; Bermudez, Beatriz Elizabeth Bagatin Veleda (Revista de Medicina, 2022)
Objective: To describe and compare the nutritional habits, physical activity, and body mass index (BMI) of children and adolescents with Down syndrome followed up in the specialized outpatient clinic of a tertiary hospital in southern Brazil. Method: Cross-sectional study conducted from the analysis of medical records of patients with Down syndrome at school age and adolescents followed up at the Complexo Hospital de Clínicas of the Universidade Federal do Paraná. The diet was considered adequate if it consisted of foods from all groups in the three main meals and one or two snacks and water in the intervals. A sedentary lifestyle was defined as physical activity time of fewer than 300 minutes per week. Nutritional status was assessed using BMI curves from the World Health Organization, 2007. Results: The study included 755 patients, of whom 236 (31.3%) were children and 519 (68.7%) were adolescents. Overweight and obesity were observed in 10.7% and 14.8% of the population, respectively, without significant gender differences. Inadequate diet was observed in 34.6% and sedentarism in 23.7% of the patients. High BMI was observed in 20.3% of children and 27.9% of adolescents (p=0.026). Sedentarism was observed in 29.5% of adolescents and 11% of children (p<0.001). Inadequate diet was also more prevalent in adolescents but without statistical difference. Patients with high BMI, compared to eutrophic patients, had a higher prevalence of inadequate diet and sedentarism, with statistical significance. In this subgroup, sedentarism was observed in 25% of children and 57.2% of adolescents (p<0.001). Conclusion: Adolescents with Down syndrome have higher rates of high BMI and sedentarism compared to children. Specific studies in health education for this population are necessary to promote healthy lifestyle habits and effectively prevent obesity.